PENDIDIKAN ISLAM PERSPEKTIF BUYA HAMKA: RELEVANSINYA TERHADAP PENGUATAN KESEHATAN MENTAL GEN Z - Nisa’, Mas Ayu Ainun; Salik, Mohamad; Fahmi, Muhammad; Hamidah, Hamidah; Tarik, Atika Agustina (STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
The mental health issues faced by Gen Z are becoming increasingly complex due to rapid technological advancements and socio-cultural changes. Social pressures from social media, unrealistic self-comparisons, academic stress, demands for success, and excessive use of social media can exacerbate Gen Z's mental health conditions. Psychological support and holistic education are necessary to address these challenges. Buya Hamka offers an Islamic educational concept that can serve as an alternative in tackling the mental health crisis. This study employs a library research method and aims to explore the relevance of Buya Hamka's perspective on Islamic education in supporting Gen Z's mental health. The findings reveal that Buya Hamka's concept of Islamic education emphasizes the importance of aqidah (faith), akhlaq (morality), and the balance between intellect and soul in strengthening Gen Z's mental health. Aqidah provides a sense of life purpose, while akhlaq helps in managing emotions and social relationships. The balance between intellect and soul supports decision-making and emotional needs. This approach demonstrates the relevance of Islamic education from Buya Hamka's perspective in strengthening Gen Z's mental health.